Pathophysiology of als: What and how much do we know? [Als patofi̇zyoloji̇si̇: Neyi̇, ne kadar bi̇li̇yoruz?] - (:unkn) unknown (My University, 2008)
Amyotrophic lateral sclerosis is a progressive neurodegenerative disorder, primarily involving motor neurons in the cerebral cortex, brainstem and spinal cord. Most cases are sporadic, although 5-10% are familial, with 10-20% being linked to mutations in the enzyme superoxide dismutase-1. The clinical and pathological features of familial and sporadic cases are strikingly similar. In this review, the proposed mechanisms underlying the pathophysiology of ALS are focused with a hypothetical integrative model.
Keywords: ALS; Hypothetical integrative model; Pathophysiology